Chemical taphonomy and preservation modes of Jurassic spinicaudatans from Patagonia: A chemometric approach - Monferran, Mateo Daniel (2018)
Spinicaudatans ('clam shrimps') are small branchiopod crustaceans enclosed in a chitinous bivalved carapace that is often the only preserved element in the fossil record. However, few studies have analyzed the preservation of these carapaces, which have been found in continental facies from the Devonian to the present. The aim of this study was to contribute to a better understanding of the chemical preservation of fossil spinicaudatan carapaces, and it focused on spinicaudatan carapaces of the Cañadón Asfalto Formation from the Jurassic of Argentina. Semiquantitative energy-dispersive X-ray spectrometry (EDS) analysis provided elemental composition data that were interpreted using principal component analysis (PCA). The results showed a complex chemical mode of preservation for spinicaudatan carapaces. In some parts, EDS spectra of the specimens exhibit peaks of calcium, phosphorous, aluminum, and fluorine, representing the retention of original carapace material with some diagenetic recrystallization. Certain zones of the carapace show low-intensity peaks of the elements mentioned, while silicon and oxygen peaks (from the rock matrix) become the dominant spectral signals. These modes of preservation modify the interpretations and observations of the ornamentation of the carapace, which are used as taxonomic features. Our results suggest that specific diagenetic processes play a fundamental role in the preservation of spinicaudatans.